2014
DOI: 10.3389/fcimb.2014.00087
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Mycobacterium avium subsp. paratuberculosis mutants for attenuation in a bovine monocyte-derived macrophage model

Abstract: Vaccination remains a major tool for prevention and progression of Johne's disease, a chronic enteritis of ruminants worldwide. Currently there is only one licensed vaccine within the United States and two vaccines licensed internationally against Johne's disease. All licensed vaccines reduce fecal shedding of Mycobacterium avium subsp. paratuberculosis (MAP) and delay disease progression. However, there are no available vaccines that prevent disease onset. A joint effort by the Johne's Disease Integrated Prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…Each dot represents one individual response, the middle line represents the average in each group, and the error bars represent SD from the mean in each group. the concentration of NO − and bactericidal activity has been reported in rats and chickens but not in mice and cattle (Weiss et al, 2002;Sun et al, 2008;Guimarães et al, 2011;Zhao et al, 2013;Lamont et al, 2014;Akhtar et al, 2016;Qin et al, 2016). Lack of the ability to reliably measure macrophage function, including the production of NO − , seems to be the source of inconsistency.…”
Section: Discussionmentioning
confidence: 99%
“…Each dot represents one individual response, the middle line represents the average in each group, and the error bars represent SD from the mean in each group. the concentration of NO − and bactericidal activity has been reported in rats and chickens but not in mice and cattle (Weiss et al, 2002;Sun et al, 2008;Guimarães et al, 2011;Zhao et al, 2013;Lamont et al, 2014;Akhtar et al, 2016;Qin et al, 2016). Lack of the ability to reliably measure macrophage function, including the production of NO − , seems to be the source of inconsistency.…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence for the transposon insertions affecting the functions of Mod operon (e.g., MAP1566 or MAP1567) is provided by the similar properties of both mutants in MDMs, mice (Bannantine et al, 2014 ) and goats (Hines et al, 2014 ). These mutants were attenuated in C57BL/6 mice but protective against wild type challenge, displayed low skin reactivity in goats and showed significant attenuation in MDM assays as analyzed elsewhere (Lamont et al, 2014 ). However, in this current analysis, 30H9 and STM68 were comparable to the wild type strain.…”
Section: Discussionmentioning
confidence: 77%
“…Isolate 22F4 carries an insertion within the gene encoding the Lsr2 protein that has been implicated in various roles: dominant T cell responses in MTB (Stewart et al, 2002 ) and biofilm formation and colony morphology in Msmeg (Chen et al, 2006 ). Furthermore, a MAP lsr2 deletion mutant has been constructed (Park et al, 2008 ) that showed similar properties and a marginal degree of attenuation in MDMs to 22F4 (Lamont et al, 2014 ), thus providing strong evidence that the transposon insertion, that is internal to lsr2 , does disrupt the function of this gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scandurra et al (2010) were able to classify the strains according to their virulence and made a preliminary selection of vaccine candidates in a well-defined bovine monocytederived macrophage model. However, some studies have highlighted the limitations of the macrophage model in the initial screening of Map virulence and in predicting vaccine candidates (Bannantine et al, 2014b;Lamont et al, 2014). Vaccine trials in goat, sheep, deer or bovine hosts are highly costly and thus the use of small animal models such as mice facilitate comparisons between different vaccine trials.…”
Section: Introductionmentioning
confidence: 99%